Toward improved myocardial maturity in an organ-on-chip platform with immature cardiac myocytes. Issue 17 (November 2017) - Sheehy, Sean P; Grosberg, Anna; Qin, Pu; Behm, David J; Ferrier, John P; Eagleson, Mackenzie A; Nesmith, Alexander P; Krull, David; Falls, James G; Campbell, Patrick H; McCain, Megan L; Willette, Robert N; et al.
In vitro studies of cardiac physiology and drug response have traditionally been performed on individual isolated cardiomyocytes or isotropic monolayers of cells that may not mimic desired physiological traits of the laminar adult myocardium. Recent studies have reported a number of advances to Heart-on-a-Chip platforms for the fabrication of more sophisticated engineered myocardium, but cardiomyocyte immaturity remains a challenge. In the anisotropic musculature of the heart, interactions between cardiac myocytes, the extracellular matrix (ECM), and neighboring cells give rise to changes in cell shape and tissue architecture that have been implicated in both development and disease. We hypothesized that engineered myocardium fabricated from cardiac myocytes cultured in vitro could mimic the physiological characteristics and gene expression profile of adult heart muscle. To test this hypothesis, we fabricated engineered myocardium comprised of neonatal rat ventricular myocytes with laminar architectures reminiscent of that observed in the mature heart and compared their sarcomere organization, contractile performance characteristics, and cardiac gene expression profile to that of isolated adult rat ventricular muscle strips. We found that anisotropic engineered myocardium demonstrated a similar degree of global sarcomere alignment, contractile stress output, and inotropic concentration–response to the β-adrenergic agonist isoproterenol. Moreover, the anisotropic engineered myocardium exhibited comparable myofibril related gene expression to muscle strips isolated from adult rat ventricular tissue. These results suggest that tissue architecture serves an important developmental cue for building in vitro model systems of the myocardium that could potentially recapitulate the physiological characteristics of the adult heart. Impact statement: With the recent focus on developing in vitro Organ-on-Chip platforms that recapitulate tissue and organ-level physiology using immature cells derived from stem cell sources, there is a strong need to assess the ability of these engineered tissues to adopt a mature phenotype. In the present study, we compared and contrasted engineered tissues fabricated from neonatal rat ventricular myocytes in a Heart-on-a-Chip platform to ventricular muscle strips isolated from adult rats. The results of this study support the notion that engineered tissues fabricated from immature cells have the potential to mimic mature tissues in an Organ-on-Chip platform.